RELASI SUBJEK, OBJEK, DAN NILAI PADA PENCIPTAAN KARYA FOTOGRAFI SENI NICO DHARMAJUNGEN - Damarjati, FX (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2023)
In the discourse of fine arts, photography is a medium for expressing the expression of its artists whose practice has been similar to other processes of art creation. Expressive photography has become more subjective than other genres such as journalistic and commercial. It is this difference that makes expression photography an interesting discourse to research from the creation process, the embodiment of the work to the presentation technique. An important element in the process of embodiment of expressive photography is the relationship between the subject, object and the value of the artist’s thoughts. The subject as a photographer/creator/artist undergoes aesthetic and artistic experiences that are heavily influenced by his own history, formal education in art schools, experience of undergoing continuous photography practice, experience of observing and seeing the development of photography both in Indonesia and western country. It is this influence that makes the subject become more mature in choosing objects so that they have value and meaning for their photography career journey as well as being wiser in choosing the stories implied in their photographic works of art. In this study, the figure of Nico darmajungen was deliberately chosen considering the criteria above in accordance with his figure. Moreover, his photography styles have brought about a change in the paradigm of photography in Indonesia. The conclusion of this study is that the aesthetic experience experienced by artists and spectators becomes a major stage before works of art are created. Aesthetic experience has stimulated the brain to create works in accordance with the artistic experience that is practiced. The stages that occur subconsciously but are always repeated in the creation of a work of art seem to be a bridge to read an artist’s creative process.Keywords: Art Photography, Nico Dharmajungen, Art Objects, Art Value, Art Subjects